Temperature‐dependent effects of house fly proto‐Y chromosomes on gene expression could be responsible for fitness differences that maintain polygenic sex determination. Issue 22 (7th September 2021) - Adhikari, Kiran; Son, Jae Hak; Rensink, Anna H.; Jaweria, Jaweria; Bopp, Daniel; Beukeboom, Leo W.; Meisel, Richard P.
Abstract: Sex determination, the developmental process by which sexually dimorphic phenotypes are established, evolves fast. Evolutionary turnover in a sex determination pathway may occur via selection on alleles that are genetically linked to a new master sex determining locus on a newly formed proto‐sex chromosome. Species with polygenic sex determination, in which master regulatory genes are found on multiple different proto‐sex chromosomes, are informative models to study the evolution of sex determination and sex chromosomes. House flies are such a model system, with male determining loci possible on all six chromosomes and a female‐determiner on one of the chromosomes as well. The two most common male‐determining proto‐Y chromosomes form latitudinal clines on multiple continents, suggesting that temperature variation is an important selection pressure responsible for maintaining polygenic sex determination in this species. Temperature‐dependent fitness effects could be manifested through temperature‐dependent gene expression differences across proto‐Y chromosome genotypes. These gene expression differences may be the result of cis regulatory variants that affect the expression of genes on the proto‐sex chromosomes, or trans effects of the proto‐Y chromosomes on genes elswhere in the genome. We used RNA‐seq to identify genes whose expression depends on proto‐Y chromosome genotype and temperature in adult male house flies. We found no evidence for ecologically meaningful temperature‐dependent expression differences of sex determining genes between male genotypes, but we were probably not sampling an appropriate developmental time‐point to identify such effects. In contrast, we identified many other genes whose expression depends on the interaction between proto‐Y chromosome genotype and temperature, including genes that encode proteins involved in reproduction, metabolism, lifespan, stress response, and immunity. Notably, genes with genotype‐by‐temperature interactions on expression were not enriched on the proto‐sex chromosomes. Moreover, there was no evidence that temperature‐dependent expression is driven by chromosome‐wide cis ‐regulatory divergence between the proto‐Y and proto‐X alleles. Therefore, if temperature‐dependent gene expression is responsible for differences in phenotypes and fitness of proto‐Y genotypes across house fly populations, these effects are driven by a small number of temperature‐dependent alleles on the proto‐Y chromosomes that may have trans effects on the expression of genes on other chromosomes.